Solvency, Profitability, and Financial Performance - Hermala Kusumadewi; Evieana Riesty Saputri; Andriono Eko Yuniarto (Telaah Bisnis, 2023)
This study set out to ascertain how solvency and profitability impacted financial performance. Using a purposive sampling technique, a mining business in the coal subsector that will be listed on the Indonesia Stock Exchange between 2016–2022, serves as the research sample. The debt to equity ratio (DER) is used to assess the solvency variable. Total assets turnover (TATO), a measure of asset utilization, and net profit margin (NPM), a measure of operating performance, are used to measure the profitability variable. Return on total assets (ROA) is a metric used to assess financial performance. The findings of this study show that all independent variables—DER, TATO, NPM, and ROA—affect the dependent variable of financial performance simultaneously and partially.